Konsumsi Air Kajian Kelayakan Sumur Perumahan Tipe 36 di Kota Pekanbaru - Rahmadega Hertisa (Universitas Riau, 2018)
The purpose of this study is to analyze well water consumption properness, to analyze the effect of length septic tank to well water properness, and to analyzethe effect of soil type to well water consumption properness of type 36 housing in Pekanbaru. The method of this study is quantitative with cross sectional. Based on the analysis result, it is found that the feasibility of the well water consumption in the type 36 housing in Pekanbaru City on the turbidity parameter is only Rumbai Sub-district exceeding the quality standard, Escherichia coli parameter or total coliform exceeds the standard quality, pH parameter has acid water does not reach the quality standard. The influence of the distance of the fecal container tube with the feasibility of the well water of type 36 housing in Pekanbaru City is the parameter of Escherichia coli or total coliform by using chi-square test has correlation or interplay relationship ≤ 0.05. The influence of soil type that is found on the feasibility of well water of type 36 housing in Pekanbaru City is on Escherichia coli parameter by using chi-square test has correlation or interrelation relationship ≤ 0.05. The results of the analysis of the water wellness feasibility of type 36 housing in Pekanbaru City is evaluated from the aspect of the quality of physical, biological, chemical parameters, related to the effect of distance and type of well water to the fecal reservoir.